Effectiveness of The Luo Yuan Technique in Patients with Hyperuricemia, Case Report - Laura, Patricia Nava González; Michelle, Christlieb Rivera Ortiz; Rebeca, Alejandra Avendaño Espina (International Journal of Complementary Medicine, 2025)
Significance This case report describes the alternative management of hyperuricemia through acupuncture using the Luo Yuan technique. Case presentation A 53-year-old Mexican man was diagnosed with secondary hyperuricemia. The patient began to experience arthralgia in the metatarsophalangeal joint of the first toe on his left foot after consuming a high amount of purine-rich foods, with a 10-year history. The symptoms were sporadically controlled with the use of colchicine and indarzone. In a six-element blood chemistry test, serum uric acid was 8.7 mg/dL before acupuncture treatment and 8.3 mg/dL at the end of treatment, without applying dietary restrictions on purine consumption. Conclusions and relevance This report demonstrates the potential efficacy of acupuncture at the Luo and Yuan points of the Spleen and Stomach meridians in reducing elevated blood uric acid levels. This suggests its potential as an alternative treatment for patients with hyperuricemia and other metabolic disorders.
Keywords: Hyperuricemia; Luo Yuan Technique; Acupuncture; Spleen and Stomach Meridians; Serum Uric Acid Reduction